A review of the stable isotope bio-geochemistry of the global silicon cycle and its associated trace elements - Sutton, Jill N.; André, Luc; Cardinal, Damien; Conley, Daniel J.; de Souza, Gregory F.; Dean, Jonathan R.; Dodd, Justin; Ehlert, Claudia; Ellwood, Michael J.; Frings, Patrick J.; Grasse, Patricia; Hendry, Katharine; et al. (Frontiers, 2018)
Silicon (Si) is the second most abundant element in the Earth’s crust and is an important nutrient in the ocean. The global Si cycle plays a critical role in regulating primary productivity and carbon cycling on the continents and in the oceans. Development of the analytical tools used to study the sources, sinks, and fluxes of the global Si cycle (e.g., elemental and stable isotope ratio data for Ge, Si, Zn, etc.) have recently led to major advances in our understanding of the mechanisms and processes that constrain the cycling of Si in the modern environment and in the past. Here, we provide background on the geochemical tools that are available for studying the Si cycle and highlight our current understanding of the marine, freshwater and terrestrial systems. We place emphasis on the geochemistry (e.g., Al/Si, Ge/Si, Zn/Si, d13C, d15N, d18O, d30Si) of dissolved and biogenic Si, present case studies, such as the Silicic Acid Leakage Hypothesis, and discuss challenges associated with the development of these environmental proxies for the global Si cycle. We also discuss how each system within the global Si cycle might change over time (i.e., sources, sinks, and processes) and the potential technical and conceptual limitations that need to be considered for future studies.